Aplicação de modelos epidemiológicos para determinar fatores associados a qualidade de córneas em banco de olhos - Aquino, Nathalia Mayumi Thomaz de [UNIFESP] (2016)
Objective: To develop a methodology using epidemiological models to identify factors related to transplanted cornea?s quality in Eye Banks. Methods: A case-control study was conducted to determine factors related to primary graft failure in the state of São Paulo between January 2010 and December 2013. Primary graft failure cases were defined as irreversible corneal edema in the immediately postoperative period, unresponsive to topical treatment. Controls were randomly selected from corneal transplants performed one week before or after the cases. Donors data were evaluated as cause of death, sex, age, endothelial cell count, time between death and enucleation, time to corneal preservation and preservation time before surgery. Statistical analysis between groups was performed and the odds ratio was calculated to determine factors related to primary failure. Results: Thirty-eight cases of primary graft failure were reported to the São Paulo State Transplant Center during the study period, leading to a selection of 152 controls. The cases had between 16 years to 79 years, averaging 46.1 years (SD = 16.5 years) and controls 4-79 years, mean 39.8 years (SD = 16.5 years) (p = 0.037). There were more men in both groups, 60.5% among cases and 66.4% among controls (p = 0.493). Time between death and enucleation was 4.6 hours for cases (sd = 3.7 hours) and 3.5 hours for controls (sd = 5.8horas), p = 0.255. Time between enucleation and tissue preservation was 5.7 hours (SD = 3.5 hours) for cases and 4.6 hours (SD = 5.1 hours) for controls, p 0.238. It was also verified that the time between the preservation and transplantation in cases averaged 9.5 days (SD = 2.7 days) and controls 7.9 days (SD = 2.8 days) (p = 0.001). In the multivariate analysis, each extra day of preservation increased the risk of primary failure by 23%. Regarding endothelial cell count, were verified 2518.3 cells / mm 2 (SD = 259.4 cells / mm2) in cases and 2627.0 cells / mm 2 (SD = 346.1 cells / mm2) in controls (p = 0.084). The main cause of death in both groups were cardiovascular disease (50.0% of cases and 49.3% among controls). Death from external causes were found in 18.4% of cases and 45.4% of controls. Other causes, such as cancer, accounted for 31.6% of deaths among cases and 5.3% among controls. The corneas of those who died from other causes than cardiovascular disease were 6.6 times more likely to develop primary graft failure after adjusting for other variables (odds ratio 6.6 (2.1 to 20.5)). Conclusion: The case-control study was useful to determine factors associated with primary graft failure and could be used as a tool for quality control in Eye Banks. In this study, primary graft failure was multifactorial and reflects directly the tissues quality and it?s processing. Factors such as gender, endothelial cell count, time between death and enucleation and time between enucleation and preservation were not associated with the morbidity. However, age, time between preservation and surgery and cause of death could influence the tissue?s quality, leading to higher rates of primary graft failure. Therefore, may be factors to be considered during the selection of corneas in Eye Banks.